Actively working to be more antiracist in the employee assistance field. (2nd April 2020) - Jacobson Frey, Jodi
Abstract: In addition to the ongoing response to the Novel Coronavirus Disease–2019 (COVID-19), workplaces are addressing and beginning in many cases to dismantle long-standing systems and structures that uphold racism. These changes are happening quickly and around the globe. Employee Assistance Programs (EAPs) have an opportunity to support and guide workplaces leaders as they seek out guidance and new solutions to the two pandemics of COVID-19 and racism. To start this work; however, EAPs need to work internally to examine, challenge and change their own practices and behaviors in an effort to be a more diverse, inclusive, and anti-racist work and professional environment. This article describes 10 steps EAPs can take to start or continue on their journey to be more anti-racist within their own workplaces and with the workplaces they support.